Inisiasi Penerapan Keselamatan dan Kesehatan Kerja Pada Kegiatan Pertambangan Material Konstruksi Di PT Harfia Graha Perkasa, Kabupaten Gowa, Sulawesi Selatan - Aryanti Virtanti Anas; Muhammad Ramli; Purwanto -; Asran Ilyas; Rini Novrianti Sutardjo Tui; Rizki Amalia; Andi Arjan (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
The implementation of Occupational Safety and Health (OHS) construction materials mining has not been implemented properly, including at PT Harfia Graha Perkasa. The problem faced is the lack of understanding of the importance of OHS and the potential hazards in the mining work environment both in mining, transportation and processing activities. On the other hand, there is a regulation that every mining activity must have an OHS program and standard, so the main purpose of this community service activity is to provide knowledge and understanding of OHS to mining workers. The method used is an OHS promotion program in the form of information dissemination, identification of potential hazards, and risk control efforts. The level of understanding of workers is measured through pre-test and post-test questionnaires given to 12 respondents. Prior to the initiation of the OHS program, only a total of 30% of all OSH questions were known by the workers, but after the program was carried out it was seen that there was a significant increase in the understanding of mining workers to 90%. The information dissemination program showed very good results where 100% of the information on OHS and 90% of the information on risk control efforts was known by the mine workers. This shows that service activities programs can help initiate the implementation and implementation of OHS in partner companies.